Multilayer electronic component

By integrating polydopamine-derived polymers in the side margins, the mechanical strength and moisture resistance of laminated ceramic capacitors are enhanced, addressing issues of crack susceptibility and reliability.

JP2025016334APending Publication Date: 2025-01-31SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024051300
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-24
Filing Date
2024-03-27
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Laminated ceramic capacitors face issues with mechanical strength and moisture resistance due to thin side margins, which can lead to cracks and reduced reliability.

Method used

Incorporating polydopamine-derived polymers in the side margin portions of laminated electronic components, enhancing mechanical strength and moisture resistance by improving adhesion and crack suppression.

Benefits of technology

The use of polydopamine-derived polymers in the side margins improves mechanical strength and humidity resistance, preventing crack propagation and enhancing the reliability of laminated electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016334000001_ABST
    Figure 2025016334000001_ABST
Patent Text Reader

Abstract

To provide a multilayer electronic component that excels in mechanical strength and moisture resistance reliability.SOLUTION: The multilayer electronic component includes: a body 110 including a dielectric layer and a first internal electrode 121 and a second internal electrode 122 which are alternately arranged in a first direction across the dielectric layer and including a first face 1 and a second face 2 facing each other in the first direction, a third face 3 and a fourth face 4 connected to the first and second faces and facing each other in a second direction, and a fifth face 5 and a sixth face 6 connected to the first to fourth faces and facing each other in a third direction; side margin parts 141, 142 arranged on the fifth and sixth faces; and an external electrode located on the third and fourth faces. The side margin parts include polydopamine, and the average size of a plurality of dielectric crystal particles that the side margin parts include is different from the average size of a plurality of dielectric crystal particles that the dielectric layer includes.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer electronic component. [Background technology]

[0002] Multi-layered ceramic capacitors (MLCCs), which are one type of multi-layered electronic component, are chip-type capacitors that are mounted on printed circuit boards of various electronic products, such as visual devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, and mobile phones, and serve to charge and discharge electricity. Multi-layered ceramic capacitors are small in size, yet have high capacitance, and are easy to mount, so they can be used as components in various electronic devices.

[0003] Recently, multilayer ceramic capacitors have been miniaturized to ensure the capacitance per unit volume of the multilayer ceramic capacitor, and as a result, the thickness of the side margin portion for protecting the capacitance forming portion that forms the capacitance of the multilayer ceramic capacitor has been reduced. However, the thinner the side margin portion, the weaker the mechanical strength of the multilayer ceramic capacitor, which may cause cracks or brittle fracture to occur in the multilayer ceramic capacitor. Such cracks, etc., become a path for moisture from the outside to penetrate into the multilayer ceramic capacitor, causing a decrease in the moisture resistance reliability of the multilayer ceramic capacitor.

[0004] Therefore, in order to prevent the mechanical strength and moisture resistance reliability of the multilayer ceramic capacitor from being deteriorated, research is required on a method for improving the strength of the side margin portion. Summary of the Invention [Problem to be solved by the invention]

[0005] One of several objects of the present invention is to provide a multilayer electronic component having excellent mechanical strength and moisture resistance reliability.

[0006] However, the scope of the present invention is not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]

[0007] One embodiment of the present invention provides a multilayer electronic component including a dielectric layer and first internal electrodes and second internal electrodes arranged alternately in a first direction with the dielectric layer sandwiched therebetween, a main body including a first surface and a second surface facing the first direction, a third surface and a fourth surface connected to the first surface and the second surface and facing the second direction, a fifth surface and a sixth surface connected to the first surface to the fourth surface and facing the third direction, side margin portions arranged on the fifth surface and the sixth surface, and external electrodes arranged on the third surface and the fourth surface, wherein the side margin portions include polydopamine, and an average size of a plurality of dielectric crystal grains included in the side margin portions is different from an average size of a plurality of dielectric crystal grains included in the dielectric layer. Effect of the Invention

[0008] One of the various effects of the present invention is that it can provide a multilayer electronic component having excellent mechanical strength and moisture resistance reliability. [Brief description of the drawings]

[0009] [Figure 1] 1 is a perspective view showing a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] 2 is an exploded perspective view showing a main body and a side margin portion of FIG. 1. FIG. [Diagram 3] 2 is a cross-sectional view that illustrates a cross section taken along line II' in FIG. 1. [Figure 4] 3 is a cross-sectional view that illustrates a cross section taken along the line II-II' in FIG. 2. [Diagram 5]FIG. 1 is a schematic diagram illustrating the chemical structures of (a) dopamine hydrochloride, (b) polydopamine polymer, and (c) nitrogen-doped carbonized polydopamine. [Figure 6] FIG. 5 is an enlarged view of the K1 region in FIG. [Figure 7] FIG. 5 is an enlarged view of the K2 region in FIG. [Figure 8] 4 is a graph showing a schematic analysis result of a side margin portion of a multilayer electronic component according to an embodiment of the present invention, using X-ray photoelectron spectroscopy (XPS). [Figure 9] 4 is a graph showing a result of analyzing a side margin portion of a multilayer electronic component according to an embodiment of the present invention using a Raman analysis method. [Figure 10] 1 is a perspective view illustrating a method for manufacturing a multilayer electronic component according to an embodiment of the present invention. [Figure 11] 1 is a perspective view illustrating a method for manufacturing a multilayer electronic component according to an embodiment of the present invention. [Figure 12] 1 is a perspective view illustrating a method for manufacturing a multilayer electronic component according to an embodiment of the present invention. [Figure 13] 1 is a table showing tape test results for comparative examples and examples. [Figure 14] 1 is a graph showing stress-strain curves of a comparative example and an example. [Figure 15] 1A is a graph showing the reliability evaluation results of a comparative example, and FIG. 1B is a graph showing the reliability evaluation results of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shape and size of elements in the drawings may be exaggerated for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.

[0011] In order to clearly explain the present invention in the drawings, parts that are not relevant to the explanation are omitted, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited to those shown in the drawings. Components having the same function within the same concept will be described using the same reference numerals. Furthermore, throughout the specification, when a part is said to "include" a certain component, this does not mean that other components are excluded, but that the part may further include other components, unless otherwise specified.

[0012] In the drawings, the first direction can be defined as a thickness T direction, the second direction can be defined as a length L direction, and the third direction can be defined as a width W direction.

[0013] Multilayer Electronic Components FIG. 1 is a perspective view showing a schematic view of a multilayer electronic component according to one embodiment of the present invention, FIG. 2 is an exploded perspective view showing a schematic view of the main body and side margin portion of FIG. 1, FIG. 3 is a cross-sectional view showing a schematic view of a cut section along line I-I' of FIG. 1, FIG. 4 is a cross-sectional view showing a schematic view of a cut section along line II-II' of FIG. 2, FIG. 5 is a schematic diagram showing the chemical structures of (a) dopamine hydrochloride, (b) polydopamine polymer, and (c) nitrogen-doped carbonized polydopamine, FIG. 6 is an enlarged view of region K1 of FIG. 4, FIG. 7 is an enlarged view of region K2 of FIG. 4, FIG. 8 is a graph showing the results of analyzing the side margin portion of a multilayer electronic component according to one embodiment of the present invention using X-ray photoelectron spectroscopy (XPS), and FIG. 9 is a graph showing the results of analyzing the side margin portion of a multilayer electronic component according to one embodiment of the present invention using Raman analysis.

[0014] A multilayer electronic component 100 according to one embodiment of the present invention will be described in detail below with reference to Figures 1 to 9. Also, a multilayer ceramic capacitor will be described as an example of the multilayer electronic component, but the present invention is not limited thereto and can be applied to various multilayer electronic components such as inductors, piezoelectric elements, varistors, thermistors, etc.

[0015] The multilayer electronic component 100 according to an embodiment of the present invention may include a main body 110 , side margin portions 141 and 142 , and external electrodes 131 and 132 .

[0016] Although there is no particular limitation on the specific shape of the body 110, the body 110 may have a hexahedral shape or a shape similar thereto, as shown in the drawing. Due to shrinkage of the ceramic powder contained in the body 110 during the firing process and grinding of the corners, the body 110 may have a substantially hexahedral shape, although it is not a hexahedral shape with perfect straight lines.

[0017] The main body 110 can have a first surface 1 and a second surface 2 facing in a first direction, a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and facing in a second direction, and a fifth surface 5 and a sixth surface 6 connected to the first surface 1 to the fourth surface 4 and facing in a third direction.

[0018] The main body 110 can include a dielectric layer 111 and first internal electrodes 121 and second internal electrodes 122 alternately arranged in the first direction with the dielectric layer 111 interposed therebetween. The plurality of dielectric layers 111 forming the main body 110 are in a fired state, and the boundaries between adjacent dielectric layers 111 can be integrated so as to be difficult to confirm without using a scanning electron microscope (SEM).

[0019] The dielectric layer 111 can contain, for example, a perovskite-type compound represented by ABO3 as a main component. The perovskite-type compound represented by ABO3 is, for example, BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1), Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1) or Ba(Ti 1-y Zr y )O3 (0 < y < 1).

[0020] The internal electrodes 121 and 122 can be alternately arranged with the dielectric layer 111 in the first direction. That is, the first internal electrode 121 and the second internal electrode 122, which are a pair of electrodes having different polarities, can be arranged to face each other with the dielectric layer 111 interposed therebetween. The first internal electrode 121 and the second internal electrode 122 can be electrically separated from each other by the dielectric layer 111 disposed therebetween.

[0021] The first internal electrode 121 may be disposed so as to be connected to the third surface 3, the fifth surface 5, and the sixth surface 6, and to be spaced apart from the fourth surface 4. The second internal electrode 122 may be disposed so as to be connected to the fourth surface 4, the fifth surface 5, and the sixth surface 6, and to be spaced apart from the third surface 3.

[0022] The conductive metal contained in the internal electrodes 121, 122 may be one or more of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof, and more preferably may include Ni, but the present invention is not limited thereto.

[0023] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 do not need to be particularly limited. The average thickness td of the dielectric layer 111 may be, for example, 0.1 μm to 10 μm. The average thickness te of the internal electrodes 121 and 122 may be, for example, 0.1 μm to 3.0 μm. The average thickness td of the dielectric layer 111 and the average thickness of the internal electrodes 121 and 122 can be arbitrarily set according to the desired characteristics and applications. For example, in the case of a high-voltage electronic component for electrical equipment to achieve miniaturization and high capacity, the average thickness td of the dielectric layer 111 may be less than 2.8 μm, and the average thickness te of the internal electrodes 121 and 122 may be less than 1 μm. In the case of a small-sized IT electronic component for achieving miniaturization and high capacity, the average thickness td of the dielectric layer 111 may be 0.4 μm or less, and the average thickness te of the internal electrodes 121 and 122 may be 0.4 μm or less.

[0024] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121, 122 refer to the sizes of the dielectric layer 111 and the internal electrodes 121, 122 in the first direction, respectively. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121, 122 can be measured by scanning the cross sections of the body 110 in the first direction and the second direction with a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the average thickness td of the dielectric layer 111 can be measured by measuring the thickness at a number of points, for example, 30 points that are equally spaced in the second direction, of one dielectric layer 111, and then averaging the thicknesses. In addition, the average thickness te of the internal electrodes 121, 122 can be measured by measuring the thickness at a number of points, for example, 30 points that are equally spaced in the second direction, of one internal electrode 121, 122, and then averaging the thicknesses. The 30 equally spaced points can be specified by the capacitance forming portion Ac. Meanwhile, by performing such average value measurements on 10 dielectric layers 111 and 10 internal electrodes 121, 122, respectively, and then measuring the average values, the average thickness td of the dielectric layers 111 and the average thickness te of the internal electrodes 121, 122 can be further generalized.

[0025] The body 110 may include a capacitance forming part Ac that is disposed inside the body 110 and includes first internal electrodes 121 and second internal electrodes 122 that are alternately disposed with a dielectric layer 111 therebetween to form a capacitance, and a first cover part 112 and a second cover part 113 that are disposed on both sides of the capacitance forming part Ac facing each other in a first direction. The cover parts 112 and 113 may basically serve to prevent damage to the internal electrodes due to physical or chemical stress. The cover parts 112 and 113 may have a similar configuration to the dielectric layer 111, except that they do not include internal electrodes.

[0026] The average thickness tc of the cover parts 112, 113 does not need to be particularly limited. That is, the average thickness tc of the cover parts 112, 113 can be set arbitrarily according to the desired characteristics and applications. For example, in order to reduce the size and increase the capacity of the multilayer electronic component, the average thickness tc of the cover parts 112, 113 may be 300 μm or less, 100 μm or less, 30 μm or less, or 20 μm or less, but the present invention is not limited thereto. Here, the average thickness tc of the cover parts 112, 113 means the average thickness of each of the first cover part 112 and the second cover part 113.

[0027] The average thickness tc of the cover parts 112, 113 may mean the average size of the cover parts 112, 113 in a first direction, and may be the average value of the size in the first direction measured at five points equally spaced in the second direction in the cross-sections of the body 110 in the first and second directions.

[0028] The side margin portions 141, 142 may be disposed on a fifth surface 5 and a sixth surface 6 of the body 110. Specifically, the multilayer electronic component 100 according to an embodiment of the present invention may include a first side margin portion 141 disposed on the fifth surface 5 and a second side margin portion 142 disposed on the sixth surface 6. The side margin portions 141, 142 may have a similar configuration to the dielectric layer 111, except that they do not include the internal electrodes 121, 122. That is, the side margin portions 141, 142 may include a perovskite-type compound represented by ABO3 as a main component.

[0029] The average thickness tm of the side margin portions 141, 142 does not need to be particularly limited. That is, the average thickness tm of the side margin portions 141, 142 can be set arbitrarily according to the desired characteristics and applications. For example, in order to reduce the size and increase the capacity of the multilayer electronic component, the average thickness tm of the side margin portions 141, 142 may be 100 μm or less, 20 μm or less, or 15 μm or less, but the present invention is not limited thereto. Here, the average thickness tm of the side margin portions 141, 142 means the average thickness of each of the first side margin portion 141 and the second side margin portion 142.

[0030] The average thickness tm of the side margin portions 141, 142 may mean the average size of the side margin portions 141, 142 in the third direction, and may be the average value of the sizes in the third direction measured at five points equally spaced in the first direction in a cross section of the multilayer electronic component 100 in the first and third directions passing through the center of the main body 110 in the second direction.

[0031] The external electrodes 131, 132 may be disposed outside the body 110 and connected to the internal electrodes 121, 122. The external electrodes 131, 132 may be disposed on the third surface 3 and the fourth surface 4 of the body 110 and may extend onto parts of the first surface 1, the second surface 2, the fifth surface 5 and the sixth surface 6. The external electrodes 131, 132 may include a first external electrode 131 connected to the first internal electrode 121 and a second external electrode 132 connected to the second internal electrode 122.

[0032] The external electrodes 131, 132 may include a first electrode layer disposed on the third surface 3 and the fourth surface 4 of the body 110 and connected to the internal electrodes 121, 122, and a second electrode layer disposed on the first electrode layer.

[0033] The first electrode layer may be formed by dipping the third surface 3 and the fourth surface 4 of the body 110 into a conductive paste for external electrodes containing a conductive metal and glass, followed by firing. The conductive metal contained in the first electrode layer may include Cu, Ni, Pd, Pt, Au, Ag, Pb, and / or an alloy containing these, but the present invention is not limited thereto.

[0034] Meanwhile, the first electrode layer may be composed of only one layer including metal and glass, but the present invention is not limited thereto, and the first electrode layer may have a multi-layer structure. For example, the first electrode layer may include a first layer including metal and glass and a second layer disposed on the first layer including metal and resin.

[0035] The metal contained in the second layer is not particularly limited, and may include one or more selected from the group consisting of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof. The resin contained in the second layer may play a role in ensuring bonding and absorbing shock. The resin is not particularly limited as long as it has bonding and shock absorbing properties and can be mixed with metal powder to prepare a paste, and may include, for example, one or more selected from epoxy resin, acrylic resin, ethyl cellulose, etc.

[0036] The second electrode layer can improve mounting characteristics. The type of the second electrode layer is not particularly limited, and may be a plating layer containing Ni, Sn, Pd and / or an alloy containing these, or may be formed of multiple layers. The second electrode layer may be, for example, a Ni plating layer or a Sn plating layer, or may be in a form in which a Ni plating layer and a Sn plating layer are formed in sequence. The second electrode layer may also include multiple Ni plating layers and / or multiple Sn plating layers.

[0037] In the drawings, the multilayer electronic component 100 is shown to have a structure having two external electrodes 131, 132, but this is not limited to this, and the number and shape of the external electrodes 131, 132 can be changed depending on the shape of the internal electrodes 121, 122 or other purposes.

[0038] According to an embodiment of the present invention, the side margin portions 141 and 142 may include polydopamine. Polydopamine is a polymer of dopamine, and polydopamine produced by self-polymerization of dopamine has covalently bonded catechol and imine functional groups, and can form strong bonds with both inorganic materials such as ceramic powder and organic materials such as binders.

[0039] As described later, dopamine hydrochloride shown in FIG. 5(a) may be added to a side margin forming sheet for forming side margins 141 and 142 of a multilayer electronic component 100 according to an embodiment of the present invention. The dopamine hydrochloride added to the side margin forming sheet can form a polydopamine polymer shown in FIG. 5(b) by self-polymerization. The side margin forming sheet contains a polydopamine polymer, and thus can form a strong bond with the ceramic powder and binder contained in the side margin forming sheet, thereby improving the adhesive strength of the side margin forming sheet. Therefore, when the side margin forming sheet is pressed and adhered to the side surface of the ceramic chip described later, it is possible to prevent the side margin forming sheet from peeling off from the ceramic chip.

[0040] All or a part of the polydopamine polymer contained in the sheet for forming the side margin portion may be converted to nitrogen-doped graphenated polydopamine as shown in FIG. 5(c) by undergoing a sintering process for forming the main body 110 and the side margin portions 141 and 142 of the multilayer electronic component 100. In one embodiment, at least a part of the polydopamine contained in the side margin portions 141 and 142 may be nitrogen-doped graphenated polydopamine. The nitrogen-doped graphenated polydopamine contained in the side margin portions 141 and 142 is a two-dimensional material and may improve the elastic modulus and toughness of the side margin portions 141 and 142, thereby suppressing the propagation of cracks generated in the side margin portions 141 and 142. As a result, the mechanical strength of the multilayer electronic component 100 may be improved, and ultimately, the moisture resistance reliability of the multilayer electronic component 100 may be improved.

[0041] Meanwhile, the color of the side margin portions 141, 142 may become darker due to the carbonized polydopamine contained in the side margin portions 141, 142. In one embodiment, the RGB values ​​measured at the side margin portions 141, 142 may satisfy 71≦R≦79, 71≦G≦79, and 64≦B≦72. The R value, G value, and B value of the RGB values ​​measured at the outer surfaces of the side margin portions 141, 142 may be smaller than the R value, G value, and B value of the RGB values ​​measured at the outer surfaces of the covers 112, 113, respectively, but the present invention is not limited thereto.

[0042] The side margin portion and the dielectric layer will be described in more detail below with reference to Figures 6 and 7. Figure 6 shows an enlarged view of a portion of the first side margin portion 141, but since the first side margin portion 141 and the second side margin portion 142 have substantially the same configuration, the following description is to be regarded as including all of the description of the first side margin portion 141 and the second side margin portion 142.

[0043] According to an embodiment of the present invention, an average size of the plurality of dielectric crystal grains G1 included in the side margin portion 141 may be different from an average size of the plurality of dielectric crystal grains G2 included in the dielectric layer 111. Hereinafter, the dielectric crystal grains and grain boundaries included in the side margin portion 141 may be defined as first dielectric crystal grains and first grain boundaries, respectively, and the dielectric crystal grains and grain boundaries included in the dielectric layer 111 may be defined as second dielectric crystal grains and second grain boundaries, respectively.

[0044] According to an embodiment of the present invention, the side margin portion 141 may be formed by pressing and sintering a sheet for forming a side margin portion separately from a ceramic green sheet for forming a dielectric layer. As a result, the average particle size of the first ceramic powder added to the ceramic green sheet for forming the dielectric layer 111 and the average particle size of the second ceramic powder added to the sheet for forming the side margin portion 141 may be different from each other. By making the average particle sizes of the first and second ceramic powders different, the average size of the first dielectric crystal grains G1 and the average size of the second dielectric crystal grains G2 after sintering may be adjusted to be different from each other. In addition, the nitrogen-doped carbonized polydopamine contained in the side margin portion 141 may suppress the grain growth of the first dielectric crystal grains G1, and therefore the average size of the first dielectric crystal grains G1 and the average size of the second dielectric crystal grains G2 may be different from each other.

[0045] The side margin portion 141 serves to protect the dielectric layer 111 from external moisture and external impact, and the dielectric layer 111 serves to realize the capacitance of the multilayer electronic component 100. That is, according to one embodiment of the present invention, the average size of the plurality of first dielectric crystal grains G1 and the average size of the plurality of second dielectric crystal grains G2 can be made different from each other in order to realize desired electrical characteristics and reliability.

[0046] For example, in order to improve the capacitance of the multilayer electronic component 100, the average size of the plurality of second dielectric crystal grains G2 included in the dielectric layer 111 may be larger than the average size of the plurality of first dielectric crystal grains G1 included in the side margin portion 141. Alternatively, in order to improve the reliability of the multilayer electronic component 100, the average size of the plurality of second dielectric crystal grains G2 included in the dielectric layer 111 may be smaller than the average size of the plurality of first dielectric crystal grains G1 included in the side margin portion 141.

[0047] The average size of the plurality of first dielectric crystal grains G1 contained in the side margin portion 141 does not need to be particularly limited, but may be, for example, 160 nm or more and 190 nm or less.

[0048] The average size of the plurality of first dielectric crystal grains G1 included in the side margin portion 141 may refer to an average value of the size of the dielectric crystal grains obtained by obtaining an image of a central region of the side margin portion 141 (e.g., region K1 in FIG. 4) at a magnification of 50,000 times using a scanning electron microscope (SEM) in a cross section in the first and second directions of the multilayer electronic component 100 cut at the center in the third direction, and then analyzing the image using an image analysis program, for example, the Zootos Program by Zootos Corporation.

[0049] In addition, the average size of the plurality of second dielectric crystal grains G2 included in the dielectric layer 111 may refer to an average value of the dielectric crystal grain size obtained by obtaining an image of the dielectric layer 111 arranged in the central region of the capacitance forming portion Ac (e.g., region K2 in FIG. 4) at a magnification of 50,000 times using a scanning electron microscope (SEM) in the cross section in the first and second directions of the multilayer electronic component 100 cut at the center in the third direction, and then analyzing the image using an image analysis program, for example, Zootos Program by Zootos Corporation.

[0050] In one embodiment, the polydopamine included in the side margin portion 141 may be disposed at the grain boundary GB1. The polydopamine disposed at the first grain boundary GB1 may effectively block the propagation of cracks. In addition, since the nitrogen-doped carbonized polydopamine is hydrophobic, when the nitrogen-doped carbonized polydopamine is present at the first grain boundary GB1, it may act as a barrier against moisture penetration.

[0051] Referring to FIG. 8, in one embodiment, the side margin portions 141 and 142 may have an N1s peak and a C1s peak when analyzed using X-ray photoelectron spectroscopy (XPS). When the side margin portions 141 and 142 include carbonized polydopamine doped with nitrogen, an N1s peak may be detected in addition to Ba3d5, O1s, Ti2p, and C1s peaks. That is, when N1s and C1s peaks are simultaneously detected during XPS analysis, it may be determined that carbonized polydopamine doped with nitrogen is present in the side margin portions 141 and 142. Meanwhile, the intensity of the N1s peak may have a maximum value at a binding energy of 395 eV to 405 eV, and the intensity of the C1s peak may have a maximum value at a binding energy of 280 eV to 290 eV, but the present invention is not limited thereto.

[0052] XPS analysis of the side margin portions 141, 142 can be performed on the outer surfaces of the side margin portions 141, 142, but the present invention is not limited to this, and the analysis can also be performed on cross sections in the first and second directions polished up to the center of the multilayer electronic component 100 in the third direction.

[0053] Referring to FIG. 9, in one embodiment, during Raman analysis of the side margins 141 and 142, -1 ~1380cm -1The first peak X was detected at a Raman shift of 1610 cm -1 ~1630cm -1 The second peak Y can be detected by the Raman shift of the first peak X. The first peak X can represent the D peak, and the second peak Y can represent the G peak. The first peak X and the second peak Y appear simultaneously during Raman analysis of the side margin portions 141 and 142 because the side margin portions 141 and 142 have a carbonized polydopamine structure having a two-dimensional structure.

[0054] In one embodiment, the ratio of the maximum intensity of the first peak X to the maximum intensity of the second peak Y may be 0.01 or more and 1.50 or less. The ratio of the maximum intensity of the first peak X to the maximum intensity of the second peak Y may vary depending on the defects in the carbonized polydopamine and the degree of nitrogen doping.

[0055] In one embodiment, the full width at half maximum of the first peak X is 80 cm -1 More than 90cm -1 The full width at half maximum of the second peak Y is 100 cm or less. -1 More than 110cm -1 The full width at half maximum can be the width of a peak at half the maximum intensity of the peak. The full width at half maximum of the first peak X and the second peak Y can be different depending on the defects in the carbonized polydopamine and the degree of nitrogen doping.

[0056] The Raman analysis of the side margin portions 141, 142 can be performed on the outer surfaces of the side margin portions 141, 142, but the present invention is not limited to this, and the analysis can also be performed on cross sections in the first and second directions polished up to the center of the laminated electronic component 100 in the third direction.

[0057] In one embodiment, the dielectric layer 111 does not need to contain polydopamine. When the dielectric layer 111 contains polydopamine, the mechanical strength of the dielectric layer 111 can be improved. However, when polydopamine is contained in the dielectric layer 111, which is directly related to the electrical properties of the multilayer electronic component 100, side effects such as a deterioration in the breakdown voltage of the multilayer electronic component 100 may occur.

[0058] When the dielectric layer 111 does not contain polydopamine, nitrogen may not be detected in the dielectric layer 111. In addition, when the dielectric layer 111 is analyzed using X-ray photoelectron spectroscopy (XPS), an N1s peak may not be detected. In addition, when the dielectric layer 111 is analyzed using Raman spectroscopy, an N1s peak may not be detected at 1360 cm -1 ~1380cm -1 Raman shift and 1610cm -1 ~1630cm -1 At least one of the Raman shifts may not detect a peak.

[0059] In one embodiment, the dielectric layer 111 may contain a polydopamine content that is less than the content of polydopamine contained in the side margin portions 141, 142. When polydopamine is added to the dielectric layer 111 to improve the mechanical strength of the dielectric layer 111, in order to prevent deterioration of the electrical characteristics of the multilayer electronic component 100, it is preferable to add polydopamine at a content that is less than the content of polydopamine contained in the side margin portions 141, 142. When the dielectric layer 111 contains polydopamine, the polydopamine may be disposed at the second grain boundary GB2 of the dielectric layer 111.

[0060] When the dielectric layer 111 contains polydopamine, a Raman spectrum of the dielectric layer 111 is obtained at 1360 cm -1 ~1380cm -1 A third peak was detected at the Raman shift of 1610 cm -1 ~1630cm -1The fourth peak can be detected at the Raman shift. On the other hand, since the dielectric layer 111 contains a smaller content of polydopamine than the content of polydopamine contained in the side margin portions 141 and 142, the intensity of the third peak may be lower than the intensity of the first peak X, and the intensity of the fourth peak may be lower than the intensity of the second peak Y, but the present invention is not limited thereto.

[0061] FIGS. 10 to 12 are perspective views schematically showing a method for manufacturing a multilayer electronic component according to an embodiment of the present invention. Hereinafter, with reference to FIGS. 10 to 12, an example of a method for manufacturing a multilayer electronic component 100 according to an embodiment of the present invention will be described.

[0062] First, a first ceramic slurry containing a first ceramic powder, an organic solvent, and a binder is manufactured, and the first ceramic slurry is applied and dried on a carrier film to provide a ceramic green sheet. The first ceramic powder is not particularly limited as long as a sufficient capacitance can be obtained. For example, a barium titanate-based material, a lead composite perovskite-based material, a strontium titanate-based material, or the like can be used. As examples of the ceramic powder, BaTiO3, (Ba 1-x Ca x )TiO3 (0 < x < 1) in which Ca (calcium), Zr (zirconium), etc. are partially solid-solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc. may be mentioned.

[0063] Next, as shown in FIG. 10, a first ceramic green sheet 211a and a second ceramic green sheet 211b for forming the capacitance forming portion Ac, and a first cover portion forming sheet 212 and a second cover portion forming sheet 213 for forming the cover portions 112, 113 are laminated to produce a ceramic laminate.

[0064] A first internal electrode pattern 221 for forming the first internal electrode 121 may be formed on the first ceramic green sheet 211a, and a second internal electrode pattern 222 for forming the second internal electrode 122 may be formed on the second ceramic green sheet 211b. Specifically, a plurality of first internal electrode patterns 221 may be formed on the first ceramic green sheet 211a at a predetermined interval. The plurality of first internal electrode patterns 221 may have a strip shape and be formed parallel to each other. Also, a plurality of second internal electrode patterns 222 may be formed on the second ceramic green sheet 211b at a predetermined interval. The plurality of second internal electrode patterns 222 may have a strip shape and be formed parallel to each other. The internal electrode patterns 221 and 222 may be formed by printing a conductive paste for internal electrodes including metal powder, binder, solvent, etc. using a screen printing method, a gravure printing method, etc.

[0065] On the other hand, the cover portion forming sheets 212 and 213 have a similar structure to the ceramic green sheet 211, but no internal electrode pattern is formed on the cover portion forming sheets 212 and 213.

[0066] Next, the manufactured ceramic laminate is compressed and then cut along cutting lines C1 and C2. Specifically, the ceramic laminate may be cut along a plurality of first cutting lines C1 parallel to a second direction and a plurality of second cutting lines C2 parallel to a third direction. The cutting lines C1 and C2 may cross the first internal electrode pattern 221 and the second internal electrode pattern 222.

[0067] 11 can be manufactured. In the ceramic chip 210, the cut first internal electrode patterns 221 and the cut second internal electrode patterns 222 can be alternately arranged with the cut ceramic green sheet 211 sandwiched therebetween. The cut first internal electrode patterns 221 and the cut second internal electrode patterns 222 can be exposed on both sides of the ceramic chip 210 facing in the third direction.

[0068] Next, the side margin portion forming sheets 241, 242 are provided. The side margin portion forming sheets 241, 242 are manufactured in a similar manner to the above-mentioned ceramic green sheet 211, but can be manufactured using a second ceramic slurry in which dopamine hydrochloride, a second ceramic powder, an organic solvent, and a binder are mixed. The content of dopamine hydrochloride relative to 100 parts by weight of the entire second ceramic slurry for forming the side margin portion forming sheets 241, 242 is preferably more than 0 parts by weight and not more than 2 parts by weight.

[0069] 12, side margin portion forming sheets 241, 242 are pressed and adhered to both sides in the third direction of ceramic chip 210. At this time, polydopamine polymer generated by self-polymerization improves the adhesive strength of side margin portion forming sheets 241, 242, and can prevent defects such as peeling between ceramic chip 210 and side margin portion forming sheets 241, 242.

[0070] Thereafter, the ceramic chip 210 to which the side margin sheets 241, 242 are attached is fired to form the main body 110 and the side margins 141, 142 shown in Fig. 2. The firing temperature is not particularly limited, but may be, for example, at a temperature of 1100°C or higher and 1300°C or lower. Furthermore, before firing the ceramic chip 210, a binder removal process, a barrel polishing process, etc. may be performed as necessary.

[0071] Next, the external electrodes 131 and 132 are formed. First, the body 110 on which the side margins 141 and 142 are formed is dipped into a conductive paste containing metal powder and glass, and then fired to form a first electrode layer. Meanwhile, when the first electrode layer includes a first layer containing metal and glass, and a second layer disposed on the first layer and containing metal and resin, the second layer can be formed by applying a conductive resin composition containing metal powder and resin onto the first layer, drying the composition, and then performing a curing heat treatment at a temperature of 250°C to 550°C.

[0072] Thereafter, a second electrode layer can be formed on the first electrode layer. The method for forming the second electrode layer is not particularly limited, and for example, electrolytic plating and / or electroless plating can be used.

[0073] However, the above-mentioned manufacturing method is just one example, and the manufacturing method of the multilayer electronic component 100 is not limited to the above-mentioned manufacturing method.

[0074] (Experimental Example) <Tape test> Sample chips of the examples and comparative examples were prepared by the above-mentioned manufacturing method. The sample chips in the tape test were in a ceramic chip state before firing with a sheet for forming a side margin portion attached. In the examples, 1 part by weight of dopamine hydrochloride was added to the second ceramic slurry for forming the sheet for forming a side margin portion with respect to 100 parts by weight of the second ceramic slurry in total. In the comparative examples, dopamine hydrochloride was not added to the second ceramic slurry for forming the sheet for forming a side margin portion.

[0075] FIG. 13 is a table showing the results of the tape test for the comparative example and the example. In the first condition, a tape having an adhesive strength of 1000 gf was attached to the sheet for forming the side margin portion in a direction parallel to the second direction, and then the tape was peeled off from the sheet for forming the side margin portion at a peeling speed of 3000 mm / s. In the second condition, a tape having an adhesive strength of 2200 gf was attached to the sheet for forming the side margin portion in a direction parallel to the first direction, and then the tape was peeled off from the sheet for forming the side margin portion at a peeling speed of 5000 mm / s. Then, the number of sample chips in which the sheet for forming the side margin portion had peeled off from the ceramic chip was counted among the sample chips in the comparative example and the example.

[0076] 13, in the first condition, in the comparative example, out of a total of 36 sample chips, 7 sample chips experienced peeling of the side margin portion forming sheet, whereas in the example, there was no sample chip in which peeling of the side margin portion forming sheet occurred. In the second condition, in the comparative example, out of a total of 80 sample chips, 42 sample chips experienced peeling of the side margin portion forming sheet, whereas in the example, there were 35 sample chips in which peeling of the side margin portion forming sheet occurred. This confirms that the side margin portion forming sheet of the example has superior adhesive strength compared to the comparative example due to the inclusion of polydopamine.

[0077] <Measurement of elastic modulus> Next, the elastic modulus of the sheet for forming the side margin portion was measured by measuring the linear slope of a stress-strain curve measured using a Universal Test Machine (UTM).

[0078] Fig. 14 is a graph showing the stress-strain curves of the comparative example and the example. Referring to Fig. 14, the elastic modulus of the side margin forming sheet of the comparative example was 36.7 MPa, and the elastic modulus of the side margin forming sheet of the example was 38.6 MPa. This confirms that the side margin forming sheet of the example has a higher elastic modulus than the comparative example due to the inclusion of polydopamine.

[0079] <Moisture resistance reliability test> The sample chips of the embodiment and the comparative example were prepared by the above-mentioned manufacturing method. The sample chips in the moisture resistance reliability test were in a state where the ceramic chips to which the side margin forming sheet was attached were fired and then external electrodes were formed. After that, for 400 sample chips each of the comparative example and the embodiment, a temperature of 85°C, a humidity of 85°C, and a voltage of 3.75V were applied for 8 hours, and then the change in insulation resistance IR was measured.

[0080] FIG. 15 is (a) a graph showing the reliability evaluation results of the comparative example, and (b) a graph showing the reliability evaluation results of the embodiment. Referring to FIG. 15, it can be seen that the comparative example has many sample chips in which the insulation resistance IR changes suddenly, unlike the embodiment. That is, it can be seen that the embodiment has superior moisture resistance reliability compared to the comparative example. This is because the nitrogen-doped carbonized polydopamine of the embodiment is hydrophobic, and therefore when the nitrogen-doped carbonized polydopamine is located at the grain boundary, it can act as a barrier against moisture penetration.

[0081] The present invention is not limited by the above-described embodiments and the accompanying drawings, but is limited by the scope of the accompanying claims. Therefore, within the scope of the technical idea of ​​the present invention described in the claims, various substitutions, modifications and changes are possible by a person having ordinary knowledge in the art, and these also belong to the scope of the present invention.

[0082] In addition, the expression "one embodiment" does not mean the same embodiment, but is provided to emphasize and describe each different unique feature. However, one embodiment presented above does not exclude being realized in combination with features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description that is opposite or contradictory to the matter in the other embodiment.

[0083] Furthermore, expressions such as "first, second" are used to distinguish one component from another and do not limit the order and / or importance of the components. In some cases, the first component may be named the second component, and similarly the second component may be named the first component, within the scope of the rights. [Explanation of symbols]

[0084] 100: Multilayer electronic components 110: Main unit 111: Dielectric layer 112, 113: Cover part 121, 122: Internal electrode 131, 132: External electrode 141, 142: Side margin G1, G2: Dielectric grains GB1, GB2: Grain boundary

Claims

1. a main body including a dielectric layer, and first internal electrodes and second internal electrodes alternately disposed in a first direction with the dielectric layer sandwiched therebetween, the main body including a first surface and a second surface facing the first direction, a third surface and a fourth surface connected to the first surface and the second surface and facing the second direction, and a fifth surface and a sixth surface connected to the first surface to the fourth surface and facing the third direction; Side margin portions disposed on the fifth surface and the sixth surface; external electrodes disposed on the third surface and the fourth surface; the side margin portion comprises polydopamine; The multilayer electronic component, wherein an average size of the plurality of dielectric crystal grains contained in the side margin portion is different from an average size of the plurality of dielectric crystal grains contained in the dielectric layer.

2. 2. The multilayer electronic component according to claim 1, wherein at least a portion of the polydopamine contained in the side margin portion is carbonized polydopamine doped with nitrogen.

3. a grain boundary is disposed between adjacent dielectric crystal grains among the plurality of dielectric crystal grains included in the side margin portion; The multilayer electronic component according to claim 1 , wherein the polydopamine contained in the side margin portion is disposed at the grain boundaries.

4. 2. The multilayer electronic component according to claim 1, wherein an average size of the plurality of dielectric crystal grains contained in said side margin portion is 160 nm or more and 190 nm or less.

5. 2. The multilayer electronic component according to claim 1, wherein an N1s peak and a C1s peak are detected in the side margin portion when the side margin portion is analyzed by X-ray photoelectron spectroscopy (XPS).

6. During the Raman analysis of the side margin, -1 ~1380cm -1 The first peak was detected at a Raman shift of 1610 cm -1 ~1630cm -1 The multilayer electronic component according to claim 1 , wherein the second peak is detected at a Raman shift of

7. 7. The multilayer electronic component according to claim 6, wherein a ratio of a maximum intensity of said second peak to a maximum intensity of said first peak is equal to or greater than 0.01 and equal to or less than 1.

50.

8. The full width at half maximum of the first peak is 80 cm -1 90cm or more -1 The full width at half maximum of the second peak is 100 cm or less. -1 110cm or more -1 7. The multilayer electronic component according to claim 6, wherein:

9. The laminated electronic component according to claim 1 , wherein the dielectric layer does not contain the polydopamine.

10. 2. The multilayer electronic component according to claim 1, wherein the dielectric layer contains a polydopamine content that is less than a content of the polydopamine contained in the side margin portion.

11. 2. The multilayer electronic component according to claim 1, wherein, in an analysis using X-ray photoelectron spectroscopy (XPS), an N1s peak is detected in the side margin portion, but an N1s peak is not detected in the dielectric layer.

12. During Raman analysis, the side margin was 1360 cm -1 ~1380cm -1 The first peak was detected at a Raman shift of 1610 cm -1 ~1630cm -1 A second peak was detected at the Raman shift of 1360 cm -1 ~1380cm -1 Raman shift and 1610 cm -1 ~1630cm -1 2. The multilayer electronic component according to claim 1, wherein no peak is detected in at least one of the Raman shifts.

13. During Raman analysis, the side margin was 1360 cm -1 ~1380cm -1 The first peak was detected at a Raman shift of 1610 cm -1 ~1630cm -1 A second peak was detected at the Raman shift of 1360 cm -1 ~1380cm -1 A third peak was detected at the Raman shift of 1610 cm -1 ~1630cm -1 The fourth peak was detected at the Raman shift of 2. The multilayer electronic component according to claim 1, wherein an intensity of the third peak is lower than an intensity of the first peak, and an intensity of the fourth peak is lower than an intensity of the second peak.

14. 14. The multilayer electronic component according to claim 1, wherein RGB values ​​measured at the side margin portion satisfy 71≦R≦79, 71≦G≦79, and 64≦B≦72.